Serum cytokines in primary new daily persistent headache and chronic migraine: a case control study - Cheema, Sanjay; Garr, Edmund; Mehta, Dwij; Chapman, Miles; Hart, Melanie; Lunn, Michael P.; Iodice, Valeria; Matharu, Manjit Singh (Frontiers in Neurology, 2025)
BackgroundNew daily persistent headache (NDPH) is a poorly understood headache disorder which often begins after a viral infection and has been hypothesised to have an immune basis. Several studies have found differences in peripheral serum cytokine levels between healthy controls and patients with other primary headache disorders such as migraine. We sought to measure peripheral levels of cytokines and chemokines in NDPH, chronic migraine (CM), and healthy controls, to identify any changes which could be biomarkers of inflammation in NDPH.MethodsWe performed an observational prospective case control study measuring serum cytokine levels in three age and sex matched groups of 40 patients each: patients with NDPH, patients with CM with similar headache frequency and severity, and healthy controls. We accounted for confounders such as infective or autoimmune illness, vaccinations, comorbidities, and medications. We used a 30-PLEX human cytokine immunoassay to measure the concentration of 30 cytokines and chemokines. The primary outcome measures were differences in median concentrations of TNF-α, IL-6, and IL-8 between the three groups, as these are the three cytokines found to differ between chronic migraine and healthy controls in a recent meta-analysis.ResultsAge and sex distribution was balanced between the groups. The NDPH and daily CM groups were balanced on headache frequency, severity, and duration. The concentration of IL-6 was higher in both NDPH (median 0.603 pg/mL) and CM (median 0.642 pg/mL), than in healthy controls (median 0.399 pg/mL), but there was no difference between the NDPH and CM groups. There were no significant differences in TNF-α, IL-8, or any of the other cytokines tested between the three groups.ConclusionPeripheral cytokine levels do not appear to be helpful biomarkers in differentiating NDPH from daily CM, and the lack of differences to healthy controls does not lend support to the hypothesis of neuroinflammation being involved in the pathophysiology of NDPH.